Implementing a workflow-integrated motivational interviewing training program for psychiatry trainees on an inpatient consultation-liaison rotation: lessons learned - Loveless, James P.; Rosen, Jordan H.; Yost, Joanna S. (Frontiers in Psychiatry, 2023)
Background: Effective consultation-liaison psychiatry (CLP) is proactive, collaborative, and requires providers to have proficiency with therapeutic skills beyond nosology and medication management. Motivational interviewing (MI) is an evidenced-based intervention that should be considered essential for CLP trainees to learn. Given that the demands of training and patient care are already experienced as stressful for many psychiatry trainees, the authors endeavored to create a MI training program that was integrated into trainees’ normal CLP workflow. Method: Twenty-two trainees on an inpatient CLP rotation participated in a six-week MI training program that was incorporated into their regular workflow. The program included didactic sessions with role-playing, as well as on-demand between-session coaching via an expert in MI. Trainee participation and perceptions of MI were measured via a questionnaire that was administered prior to each training session. Results: Trainee participation in the didactic sessions was inconsistent. Questionnaire data revealed positive baseline perceptions of motivational interviewing and its usefulness in inpatient medical settings. Additionally, as trainees participated in the program, perceived knowledge of motivational interviewing as well as awareness of motivational issues among their patients increased. Finally, participation in program was not perceived as disruptive to daily workflow for the participants. Discussion: This the first documented attempt at implementing a MI training program for CLP trainees that was integrated into their regular workflow. Preliminary data identified some encouraging trends, but also unexpected challenges. These lessons could inform how these types of training programs are implemented moving forward.